Renovascular hypertension elevates pulmonary ventilation in rats by carotid body-dependent mechanisms - Melo, Mariana Rosso [UNESP]; Gasparini, Silvia [UNESP]; Silva, Elaine F. [UNESP]; Karlen-Amarante, Marlusa [UNESP]; Speretta, Guilherme F. [UNESP]; Lauar, Mariana R. [UNESP]; Pedrino, Gustavo R.; Menani, Jose V. [UNESP]; Colombari, Debora S.A. [UNESP]; Zoccal, Daniel B. [UNESP]; Colombari, Eduardo [UNESP] (American Physiological Society, 2020)
The two kidney-one clip (2K1C) renovascular hypertension depends on the renin-angiotensin system and sympathetic overactivity. The maintenance of 2K1C hypertension also depends on inputs from the carotid bodies (CB), which when activated stimulate the respiratory activity. In the present study, we investigated the importance of CB afferent activity for the ventilatory responses in 2K1C hypertensive rats and for phrenic and hypoglossal activities in in situ preparations of normotensive rats treated with angiotensin II. Silver clips were implanted around the left renal artery of male Holtzman rats (150 g) to induce renovascular hypertension. Six weeks after clipping, hypertensive 2K1C rats showed, in conscious state, elevated resting tidal volume and minute ventilation compared with the normotensive group. 2K1C rats also presented arterial alkalosis, urinary acidification, and amplified hypoxic ventilatory response. Carotid body removal (CBR), 2 wk before the experiments (4th week after clipping), significantly reduced arterial pressure and pulmonary ventilation in 2K1C rats but not in normotensive rats. Intra-arterial administration of angiotensin II in the in situ preparation of normotensive rats increased phrenic and hypoglossal activities, responses that were also reduced after CBR. Results show that renovascular hypertensive rats exhibit increased resting ventilation that depends on CB inputs. Similarly, angiotensin II increases phrenic and hypoglossal activities in in situ preparations of normotensive rats, responses that also depend on CB inputs. Results suggest that mechanisms that depend on CB inputs in renovascular hypertensive rats or during angiotensin II administration in normotensive animals increase respiratory drive.
Keywords: Angiotensin; Carotid body; Renovascular hypertension; Respiration